2020
DOI: 10.1093/ecco-jcc/jjaa029
|View full text |Cite
|
Sign up to set email alerts
|

Is Therapeutic Drug Monitoring for Anti-tumour Necrosis Factor Agents in Adults With Inflammatory Bowel Disease Ready for Standard of Care? A Systematic Review and Meta-analysis

Abstract: Introduction Using therapeutic drug monitoring [TDM] in adult patients with inflammatory bowel disease [IBD] remains controversial. We conducted a systematic review and meta-analysis to answer four clinical PICO [Population, Intervention, Comparator, Outcome] questions. Methods We searched MEDLINE, Embase, Web of Science, and Cochrane Central from inception to June 30, 2019. Remission was defined by the manuscripts’ definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The available evidence is limited and of low quality, so it is difficult to ensure that 1 strategy is better than the other. 2 Retrospective designs and low power of the studies are still problems. We reach the same conclusions as Sha et al 2 and Ricciuto et al 20 : since the AGA recommendations, no prospective studies have been published to help clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available evidence is limited and of low quality, so it is difficult to ensure that 1 strategy is better than the other. 2 Retrospective designs and low power of the studies are still problems. We reach the same conclusions as Sha et al 2 and Ricciuto et al 20 : since the AGA recommendations, no prospective studies have been published to help clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…2 Retrospective designs and low power of the studies are still problems. We reach the same conclusions as Sha et al 2 and Ricciuto et al 20 : since the AGA recommendations, no prospective studies have been published to help clarify this issue. Regarding individualized dosing methods, although there are several published methods, the most widely used in IBD are those based on population PK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews and meta-analysis performed to resolve this deadlock have consistently shown no clear benefit of any TDM strategy over empiric optimization. The reviews have shown a consistent cost benefit with a reactive TDM strategy vs. empiric escalation ( 31 ) and drug durability benefit with the proactive strategy ( 32 , 33 ). This assumes greater importance in pediatrics as IBD specialists try to factor in insurance coverage and payor–payee concerns into pharmacotherapeutic decision-making ( 34 ).…”
Section: Methodsmentioning
confidence: 96%
“…Nevertheless, given the relative novelty of TDM and gaps in the literature, there continues to be uncertainty regarding the logistics of how and when to apply TDM into clinical practice [3]. Unresolved questions include how should TDM be performed-proactive monitoring vs reactive monitoring, how often should proactive testing be performed, which patients benefit most from TDM, how to interpret and respond to the results, and which are the most appropriate concentrations to target.…”
mentioning
confidence: 99%